1998
DOI: 10.1183/09031936.98.11040958
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-derived proteins in airway defence, disease and repair of epithelial injury

Abstract: One significant characteristic of the airway mucosa in vivo, that cannot easily be mimicked in vitro, is its microcirculation, which generates a highly dynamic, biologically active milieu of plasma-derived molecules that may pass to the airway lumen in vivo. New data on the mechanisms of airway mucosal exudation indicate that the protein systems of circulating plasma may contribute significantly to the biology and immunology of the lamina propria, its surface epithelium and the luminal surface, not only in inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(130 citation statements)
references
References 75 publications
(142 reference statements)
7
123
0
Order By: Relevance
“…The baseline appearance of a 2 -macroglobulin was low and consistent with previously reported baseline levels (Persson et al, 1998;Greiff et al, 2002). Furthermore, histamine produced an expected, marked mucosal output of a 2 -macroglobulin (P<0AE001).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…The baseline appearance of a 2 -macroglobulin was low and consistent with previously reported baseline levels (Persson et al, 1998;Greiff et al, 2002). Furthermore, histamine produced an expected, marked mucosal output of a 2 -macroglobulin (P<0AE001).…”
Section: Resultssupporting
confidence: 72%
“…Although this process involves movement of bulk plasma, including the largest plasma proteins such as a 2 -macroglobulin (this study), the luminal entry may not damage the epithelial lining (Erjefält et al, 1995), nor does it increase mucosal absorption, i.e. the perviousness of the epithelium to luminal solutes (Greiff et al, 1991a,b;Persson et al, 1998). We have previously suggested that this unidirectional increase in the outward permeability of the epithelial lining reflects a hydrostatic pressure-operated valve-like mechanism whereby a slight increase in the subepithelial hydrostatic pressure, created by the plasma exudate itself and its attracted fluids, allows epithelial cells to transiently separate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations